Kesiapan Sarana Dan Prasarana Dalam Implementasi Kurikulum Merdeka Di SMP Negeri Sumber Harta - Thonisiata, Evan; Danim, Sudarwan; Connie (Manajer Pendididikan, 2024)
The purpose of this study was to analyze the readiness of facilities and infrastructure in implementing the independent curriculum at Sumber Harta State Junior High School. The research design is qualitative research using a descriptive approach. The subject of this research is the principal who is the main informant. As complementary information, the research subjects were the vice principal and teachers. The data collection technique is an interview which is analyzed by data reduction, data presentation and conclusion drawing. The results of the study 1) The facilities and infrastructure needed in implementing the Merdeka Curriculum are quite adequate with a percentage of needs that have not been fulfilled only 10%. 2) The availability of facilities and infrastructure is good and quite complete because there are various facilities and infrastructure that can support learning. 3) The gap between the available facilities and infrastructure and those needed in implementing the Merdeka Curriculum is only 10%. The school is ready to implement the Merdeka Curriculum and is also one of the driving schools in Musi Rawas Regency. 4) Obstacles and challenges in terms of facilities and infrastructure in implementing the Merdeka Curriculum lie in the insufficient number of computers, laboratories, or library books to meet the needs of all students. Existing facilities and infrastructure may not be evenly distributed to all classes or subjects.